Barrett’s esophagus: results from an Italian cohort with tight endoscopic surveillance: Barrett’s Esophagus: an Italian cohort - Rodriguez-Castro, Kryssia; Crafa, Pellegrino; Franceschi, Marilisa; Franzoni, Lorella; Brozzi, Lorenzo; Ferronato, Antonio; Morini, Alice; Cuoco, Lucio; Baldassarre, Gianluca; Pertoldi, Barbara; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Barrett’s Esophagus represents a condition that predisposes to the development of esophageal adenocarcinoma. The aim of the present study was to analyze the demographic and clinical characteristics of patients with BE, to establish the presence of risk factors for this condition, and to determine the frequency of dysplastic lesions as well as the evolution towards adenocarcinoma under tight endoscopic control. Methods: In this study, we retrospectively collected and analyzed data from a cohort of patients with Barrett’s Esophagus identified through endoscopic records of ULSS7 in Northern Italy, who underwent upper esophagogastroduodenoscopy over a 10-year period from July 2008 to December 2020. Results: A total of 264 patients were identified as having BE and included in the study. Mean follow-up was 6.7 years (range: 3 months-13 years). Demographic characteristics of the study population included mean age of 62.7 years (range 33-90 years), with 62.5% of the study population being aged 60 or older, and a male predominance. Females were significantly older than males (65.7 years, range 37-90 vs 61.9 years, range 33-87, p=0.043, respectively). Conclusions: The present study confirms the importance of tight endoscopic control in the management of BE, favoring early detection of BE degeneration towards high-grade dysplasia or adenocarcinoma. In a subset of patients with high-risk factors including male sex, cigarette smoking and heavy alcohol intake, it may be worthwhile to consider endoscopic control over time in order to detect the development of BE.